ABOUT THE CONCEPTS OF STATISTICAL MEASUREMENTS - Blohin, Ye. P.; Korotenko, M. L.; Granovskyi, R. B.; Harkavi, N. Ya.; Fedorov, Ye. F.; Fylypenko, Ye. I.; Lytvynenko, O. M. (Science and Transport Progress, 2008)
There are described four concepts of the statistical measurements and the methods realizing these concepts for processing the observations. There are adduced the examples in which correct and incorrect using of the results obtained by this methods for solutions of the industrial problems are demonstrated.